INQUIRE interface for quieries in regular english - Cacnio, Nelson Q. (1998)
This project addresses the problem of how a database can be made accessible to anyone who needs to retrieve information from it at the user's most possible convenience and ease. Computer scientists and database designers have tried to provide such ease in handling database but interfaces developed for this still consist of the traditional formal SQL queries or form-based interfaces which cannot be understood by all users. Because of this problem, we have these objectives. Primarily, our project aims to develop a software that will enable ordinary users to query in a database using regular English question. This software called INQUIRE (INterface for QUeries in Regular English) will make database-handling easier. For instance, a user can employ simple, English questions such as "What are the books by Denis Ritchien" in order to retrieve the required information. In effect, this will make the database available to any person with or without computer knowledge. It will also speed up the retrieval of information from databases and will lessen expenses by eliminating the need for computer scientists in operating and maintaining databases. The long term objective of our project is to aid the process of "informating" of all the institutions or organizations that will use this software. This is because the software will allow easy access of information by all employees within the organization. This would imply better job performance or greater expertise for an individual and in the whole, for the organization or institution. Since INQUIRE is developed using a library database, library users will find it easier to look for the books they need. This paper is the framework of our project. It has several topics of discussions. First, it presents a brief history of how natural language query interfaces have developed. This is followed by a comparison between different types of database interfaces. The other chapters discuss relevant subjects: linguistic problems, system architecture, response generation, grammars and languages, parsing, and databases and SQL.